AN INSTRUCTOR'S GUIDE TO TEACHING MILITARY STUDENTS : Simple Steps to Integrate the Military Learner into Your Classroom - Bricker, Suzane L. (Rowman & Littlefield, 2017)
"An Instructor's Guide to Teaching Military Students is a resource for online and on-ground educators in private and public learning institutions around the world."--Provided by publisher.